The Russian regional convergence process: Where does it go? - Konstantin A. Kholodilin; Alexei Oshchepkov; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2009)
This paper investigates the income convergence among Russian regions in the period 1998-2006. It makes two major contributions to rather extensive literature on the regional convergence in Russia. First, it identifies spatial regimes using the exploratory spatial data analysis. Second, it examines the impact of spatial effects on the convergence process. Our results show that the overall speed of regional convergence in Russia, being low by international standards, becomes even lower after controlling for spatial effects. However, when accounting for the spatial regimes, we find a strong regional convergence among high-income regions located near other high-income regions. Our results indicate that estimation of speed of convergence using aggregate data may result in misleading conclusions regarding the nature of convergence process among Russia's regions.
Keywords: C21; O47; R12; 330; Regional convergence; -convergence; Ø-convergence; spatial regimes; spatial effects; Regionale Entwicklung; Entwicklungskonvergenz; Russland